Character Education Model Based on Ecopedagogy in Indonesia: Systematic Literature Review - Agregat Illah Nur Yanuar; Arifatul Ma’ani; Eko Purnomo; Desy Putri Purnamasari; Moh.Rafiuddin; Siti Amaliati (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to map research trends, implementation model characteristics, and recommendations for developing character education models based on ecopedagogy in Indonesia. The method employed is a Systematic Literature Review (SLR) using the PRISMA approach, with data sourced from Google Scholar via the Publish or Perish application. Of 841 identified articles, 12 articles met the inclusion criteria and were analyzed in depth. The findings reveal three key results: first, publication trends on ecopedagogy in Indonesia increased significantly in 2024–2026, although overall output remains limited; second, model implementation is concentrated at the primary education level, with three main typologies identified, namely curricular integration, institutional models based on the Adiwiyata program, and local wisdom-based models that simultaneously integrate spiritual, social, and ecological dimensions; third, development recommendations encompass a structural direction involving cross-level educational integration, a methodological direction through a Research and Development approach, and a pedagogical direction emphasizing the enhancement of teacher competence as facilitators of ecological values. These findings indicate that ecopedagogy in Indonesia has undergone a process of indigenization that enriches the global theoretical framework with locally relevant cultural and contextual wisdom values.